Neuropeptide signaling and the blood–brain barrier generate a persistent stress-induced internal state in Drosophila - Abdalla G. Alia; Xinyue Hu; Yuzhe Gu; Janviere Yau; Guangnan Tian; Julie L. Semmelhack; Kokoro Saito; Hiromu Tanimoto; Koki Tsuyuzaki; Shintaro Naganos; Tomoyuki Miyashita; Minoru Saitoe; et al. (Proceedings of the National Academy of Sciences, 2026)
Although fear conditioning has elucidated cue-evoked acute fear responses, the mechanisms by which stress experiences induce generalized internal states linked to anxiety or phobia are poorly understood. Here, we report that robust stress induces a persistent behavioral change characterized by avoidance of a confined space, claustrophobia-like behavior (CLB) in Drosophila . Unlike aversive memory formation, the development of CLB does not require dopamine receptors. Our neuronal screening determined that neuropeptide signaling via Allatostatin-A inactivates the downstream neurons via its receptor AstA-R1, causally inducing CLB. Moreover, gene expression profiling of individual fly heads revealed that innate immune response activation in the blood–brain barrier is involved in CLB. Our data demonstrate that stress-induced persistent behavioral change would not be related to a canonical mechanism of aversive memory formation, rather involves neuropeptidergic signaling and the blood–brain barrier, providing the mechanism determining internal states which persistently change into a phobia-like mode.